How Expert and Inexpert Instructors Talk about Teaching - Tracie Reding; Christopher Moore (MDPI AG, 2023)
Using mixed-method social network analysis, we explored the discussions happening between instructors within a teaching-related network and how instructional expertise correlated with the content of those discussions. Instructional expertise, defined by the extent to which effective teaching practices were implemented, was measured for 82 faculty teaching at a Midwestern research university in the USA using the Faculty Inventory of Methods and Practices Associated with Competent Teaching (F-IMPACT). Eight instructors from this population were interviewed after being selected from a stratified random sample having varied disciplines, positions, years of teaching experience, number of network alters, and quartile F-IMPACT score. Network Canvas was used to design, capture, and export network data during the interview process, and a deductive qualitative analysis approach was used for coding and analysis. In general, expert instructors had larger networks that also consisted of expert alters and greater frequency of discussions throughout the semester (both formal and informal) and participated in discussions centered around best practices and education research. Inexpert instructors had smaller teaching networks that consisted of other inexpert instructors, lower frequency of interactions, and had discussions that centered around sharing course-specific, surface-level advice.